136. Which is the optimum cylindrical phantom grid size calculation to evaluate the accuracy of gamma index for times optimizing in the pre-treatment quality assurance procedure of VMAT and IMRT tecnique?. (December 2018) - Grimaldi, L.; Monica, B. Della; Giancaterino, S.; Morandini, V.; Panese, A.; Saiani, F.; Berlinghieri, S.; Castrezzati, E.; Magnani, M.; Raspanti, D.; Pertutti, S.; Frata, P.
Abstract: Purpose: IMRT and VMAT are the state-of-the-art irradiation techniques for the delivery of highly conformal radiation fields to PTV. The use of QA tools for the verification of the planned dose distribution prior to the treatment of the patient has become a standard procedure in clinical routine. Aim of this study is to evaluate the optimal grid size calculation on cylindrical phantoms to determine the gamma index ( γ ) levels for the routinely pre-treatment dosimetric QA. Methods and materials: The measurements were made on a Elekta Precise linear accelerator and compared with the created plans by the Philips Pinnacle 3 TPS. The pre-treatment evaluations were made with the PTW_OCTAVIUS-4D phantom with the 729 cubical ion chambers arranged in the OCTAVIUS_Detector 2D_array of 27 cm × 27 cm. The beam incidence is always perpendicular to the surface of the detector panel and the data were collected and evaluated by means of the PTW_VeriSoft software package. On about 100 patients who underwent to radiotherapy with VMAT, were evaluated the γ between the dose deliveries and the dose calculations on the cylindrical phantom with cubic step size of 4 mm, 3 mm and 2 mm. For each phantom grid size the γ value with [3 mm;3%], [2 mm;2%] and [1 mm;1%] as distance and dose difference criteria respectively were determined. Results: For each fixed γ [d(mm);D(%)] criteria the γ global ratios to the 3 mm voxel phantom calculation, followed a Gaussian distribution. That mean that there isn't a correlation between the used phantom grid size and γ accordance. The agreement in γ differences were found within 2%(2SD), 3%(2SD) and 5%(2SD) for γ [3 mm;3%], γ [2 mm;2%] and γ [1 mm;1%] respectively. Conclusions: Due to the computer limits and the large amount of calculation, the TPS algorithms are often time consuming, strongly depending on the set grid size calculation. For a busy Center a voxel grid size of 3–4 mm is enough appropriate.